Implementasi Good Corporate Governance Pada Bank Syariah - Nabila Khairina; Nurul Inayah (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
This study aims to analyze the implementation of GCG principles in the Bank Syariah. GCG is a crucial field in the banking world for transparency, accountability, and compliance with regulations. The research uses data collection, and observation to provide better understanding of how BankSyariah has implemented GCG principles.